Program Pemberdayaan dan Pengembangan Kewirausahaan Pondok Pesantren Mahasiswa Ma’arif NU Kota Metro Melalui Karya Seni Kaligrafi - Hanif Amrulloh; Rizky Hidayatullah; Agus Setiawan; Ahmad Zarnuji; Dedi Setiawan; Jaenullah Jaenullah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Islamic boarding schools for students are Islamic educational institutions with a boarding system in which students from Islamic boarding schools have Islamic religious education and general knowledge from universities. The Islamic Student Boarding School of the Ma'arif NU Islamic Institute in Metro City is located in Metro, Lampung. So far, there are approximately 70 students at the Ma'arif NU student boarding school in Metro City. There are prospects for advancement in entrepreneurial skills centered on this opportunity. To improve students in general education and Islamic scholarship, but with other skills currently needed, one of which is entrepreneurship. Making calligraphy art with tremendous economic potential is one of the skills taught in Islamic boarding schools. The goals of this program include introducing entrepreneurship to student students, learning how to use Prada techniques to create calligraphy art, and applying calligraphy art-making as an entrepreneur. The ABCD method was used for the assistance given to Metro City Ma'arif NU Islamic boarding school students. In this strategy, service prioritizes using capacity and assets that the group already has. In this approach, the capacity or potential is the direct assistance of society in achieving progress. The assistance results showed that the students managed to develop a calligraphy company that was run at an entire profit to fund the needs of the Islamic boarding school students. Students are not solely dependent on parental submissions based on these benefits. The outcomes of the calligraphy efforts carried out will fulfill the needs of entrepreneurial learners.